Risk Management Strategies in Construction Organizations - Alhammadi, S.A. (Bentham Science Publishers, 2021)
Background: Construction projects are among the riskiest businesses due to the number of factors involved that are difficult to control; hence, the popularity of risk management as part of the decision-making process in construction organizations is increasing. Despite the advancements, there are various risks involved that lead to project failure. Aim: Thus, this study aims to assess the risk management strategies in construction organizations in the Gaza Strip, Palestine. Methods: Seventy questionnaires were distributed after subjecting them to pretesting and pilot study that confirmed the validity and reliability of the questions. The target respondents included engineers and consultants from the construction organizations, Ministry of Works and Housing, and international agencies. The questionnaire was retrieved with a 65.71 response rate. Results: Results indicated that the most popular method of risk factor determination in the Gaza Strip is the âchecklistâ (RII=84). For tools/methods of risk analysis, relying on experience in the direct assessment is the most prominent, with an RII of 78. For the methods of avoiding risk before the project implementation, dependence on experience in the work for preparing and planning was ranked highest (having RII of 81.6). Finally, follow-up on the implementation to avoid rework, with an RII of 77.6, was ranked highest among other factors of avoiding risk during the construction projects implementation. Conclusion: This study highlights the key risk management strategies that will be beneficial for the construction industry stakeholders to resolve the unwanted risk failures in the construction industry. Â© 2021 Alhammadi et al.